A novel SO2 probe inhibits lysophagy induced by Senecavirus A infection by promoting LAMP1 Cys375 sulfenylation - Wang, Shuo; Han, WenWen; Zhao, BaoXiang; Hong, Ye; Li, Jun; Miao, JunYing; Lin, ZhaoMin (PLOS Pathogens, 2026)
Lysophagy plays a key role in maintaining autophagy homeostasis, but the induction and regulation mechanisms of lysophagy are not clear. In this study, we found that Senecavirus A (SVA) dramatically decreased lysosomal-associated membrane protein 1(LAMP1), significantly increased lysosomal permeability, and induced lysophagy. We demonstrated that the SO2 probe (2-(4-(dimethylamino-) phenyl)1,1, 3-trimethyl-1h-benzo [e] indole-3-ium, DLC) could inhibited the degradation of LAMP1 and reduced lysophagy caused by SVA infection. DLC directly binds to LAMP1, and enhanced sulfenylation modification of LAMP1 at Cys375 to inhibit non-lysine ubiquitination. Finally, we verified the antiviral effects of DLC in cells and in BALB/c mice. Taken together, our study lays the foundation for the identification of SVA infection targets and the development of antiviral drugs in the future.